2010
DOI: 10.1118/1.3298015
|View full text |Cite
|
Sign up to set email alerts
|

Organ doses to adult patients for chest CT

Abstract: Purpose: The goal of this study was to estimate organ doses for chest CT examinations using volume computed tomography dose index ͑CTDI vol ͒ data as well as accounting for patient weight. Methods: A CT dosimetry spreadsheet ͑ImPACT CT patient dosimetry calculator͒ was used to compute organ doses for a 70 kg patient undergoing chest CT examinations, as well as volume computed tomography dose index ͑CTDI vol ͒ in a body CT dosimetry phantom at the same CT technique factors. Ratios of organ dose to CTDI vol ͑f o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 18 publications
(14 reference statements)
2
35
0
Order By: Relevance
“…Our study shows that the lung dose in CT of thorax imaging is 9.1 and 2.1 mGy for 120 kV and 80 kV respectively. In a study by Huda et al (25) , organ dose in CT was reported based on dose measurements on CTDI phantom. In this study dose in lung and heart were 6.8 mGy and 10.3 mGy respectively with 120 kV, 100 mAs and 12 cm scan length.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that the lung dose in CT of thorax imaging is 9.1 and 2.1 mGy for 120 kV and 80 kV respectively. In a study by Huda et al (25) , organ dose in CT was reported based on dose measurements on CTDI phantom. In this study dose in lung and heart were 6.8 mGy and 10.3 mGy respectively with 120 kV, 100 mAs and 12 cm scan length.…”
Section: Discussionmentioning
confidence: 99%
“…Dose to transverse process and spinous process are more than body of spine. In most studies, organ dose was calculated based on dose measurements in CTDI phantom (25)(26)(27) . In these studies, organ dose level was reported for a reference man and was not patient speci ic.…”
Section: Discussionmentioning
confidence: 99%
“…Data have been presented that can correct for patient body size in chest, cardiac, and abdominal imaging by modeling patients as mass equivalent cylinders of water, and making use of published scientific data on relative doses in cylinders of varying diameter. 33,35,36 In the chest, for example, it has been shown that a 50 kg patient is expected to have doses that are 18% higher than those in a 70 kg adult, whereas a 100 kg patient will have doses that are 18% lower. 33 When using R K values for estimating patient organ doses, it is essential that appropriate corrections are applied to take into account patient size.…”
Section: 27mentioning
confidence: 99%
“…33,35,36 In the chest, for example, it has been shown that a 50 kg patient is expected to have doses that are 18% higher than those in a 70 kg adult, whereas a 100 kg patient will have doses that are 18% lower. 33 When using R K values for estimating patient organ doses, it is essential that appropriate corrections are applied to take into account patient size. Turner et al have shown as an extension to their earlier work, that patient size corrections are feasible for CTDI-based organ dose estimates in abdominal CT examinations.…”
Section: 27mentioning
confidence: 99%
See 1 more Smart Citation